Internal Monologue in James Joyce’s Ulysses - Dlnya Abdalla Mohammed Ali (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The term interior monologue depicts the continuous flow of contemplations and awareness inside the waking mind. It is a narrative strategy that attempts to grant the written equivalent of the method of individual reflection; it successfully embodies the character’s complete mental process, thoughts and feelings. In literature, the term alludes to the stream of these ideas, with reference to the method of looking at a specific personality. Modernists utilize this device to show a story in the shape of individual contemplations instead of employing a dialogue or depiction. In this paper light is shed on two different kinds of interior monologue; direct and indirect and the differences between them are displayed, later descriptive qualitative method is used to identify and analyze the direct interior monologues that is used by the three main characters in Joyce’s Ulysses (1922) which is considered as the greatest work of modern English literature today. So, there will be no discussion about indirect interior monologue in this research.